Effect of biofertilizers in the vegetative phase of the onion crop (Allium cepa L.) - Alvarez_Arias, Celinda (2022)
The objective of the research was to evaluate the effect of earthworm humus, bovinase and whosease in the vegetative phase and yield of the onion (Allium cepa L.) red variety Arequipa. The study was carried out in the district of Curpahuasi, province of Grau, department of Apurímac. The study variables were plant height, number of leaves, bulb height, bulb diameter and onion crop yield. With a completely randomized block design. The results showed significant differences (Sig.<0.05) reporting a higher plant height with the application of Worm Humus with a dose of 10.8 t/ha, while the highest number of leaves was found with the application of Bovinase at a dose of 20 t/ha. The production yield was found with the Earthworm Humus (9.8 t/ha) higher compared to the other biofertilizers, being non-significant (Sig. > 0.05) when compared with the other treatments, no significant differences were recorded (Sig. > 0.05 ) between the average weight of bulbs and yields. It is concluded that the application of earthworm humus with a dose of 10.8 t/ha is recommended in the production of Arequipa red onion.